STUDI KELAYAKAN INVESTASI PEMBANGUNAN RS SEHAT BAHAGIA PEKANBARU - , Yos Hendra, Prof. Dr. Eduardus Tandelilin, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Pekanbaru has various types of health service provider, i.e. community health center, private practitioner, private clinic and hospitals. Demand for health care services in Pekanbaru is high and is considered as profitable business opportunity. Building a hospital needs a feasibility study. The aim of this feasibility study to Sehat Bahagia Hospital in Pekanbaru is to assess suitability of investment. Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PP) analysis were used in this study. Primary and secondary data were used in the analysis. Primary data are community perception on current hospital performance in Pekanbaru. Secondary data were collected from internet, health offices, social offices, and Center for Statistics Bureau. Analysis of Net Present Value resulted in positive value of IDR 211.601.679.237. Internal Rate of Return is 18 percent, which is higher than discount factor. Payback Period is eight years and eight months, which is shorter than projection. This financial analysis concludes that it is financially feasible to build Sehat Bahagia Hospital.